Risk aversion and sorting into public sector employment - Christian Pfeifer (Institute for the Study of Labor (IZA), 2008)
This research note uses two German data sets the large-scale German Socio-Economic Panel and unique data from own student questionnaires to analyse the relationship between risk aversion and the choice for public sector employment. Main results are: (1) more risk averse individuals sort into public sector employment, (2) the impact of career specific and unemployment risk attitudes is larger than the impact of general risk attitudes, and (3) risk taking is rewarded with higher wages in the private but not in the public sector.
urn:nbn:de:101:1-20080527239
Keywords: J24; 330; Public sector; risk aversion; sorting; wage differentials; Studierende; Berufswahl; Risikoaversion; Öffentlicher Dienst; Lohnstruktur; Deutschland